Reassessing the Value of Contrast-Enhanced Ultrasonography in Differential Diagnosis of Cervical Tuberculous Lymphadenitis and Lymph Node Metastasis of Papillary Thyroid Carcinoma - Zhang, Xu; Wang, Lingling; Feng, Na; Ni, Tu; Tang, Wei (Frontiers in Oncology, 2021)
Aim: The objective of this study was to retrospectively evaluate the diagnostic accuracy of contrast-enhanced ultrasonography (CEUS) in differentiating between cervical tuberculous lymphadenitis and lymph nodes metastatic from papillary thyroid cancer (PTC). Methods: One hundred two cervical lymph nodes were evaluated using conventional ultrasonography (US) and CEUS before biopsy. We determined the diagnostic indices of individual sonographic features for differentiating between metastatic and tuberculous lymph nodes by comparing the US, CEUS features and time–intensity curve (TIC) with the final diagnoses. TIC includes time to peak (TP), peak intensity (PI), and area under the gamma curve (AUC). Results: Pathologic results showed that 48 of the 102 enlarged lymph nodes were lymph node metastasis from PTC, 54 were tuberculous lymphadenitis. Hyperechoic islands, Pulse-like enhancement and Asynchronous enhancement differences were statistically significant in tuberculous lymphadenitis and lymph node metastasis (P <0.05), but their diagnostic sensitivity and specificity were not satisfactory. There was no significant statistical difference between Enhancement direction, Enlarged range on CEUS, and Perfusion defect(P >0.05). No significant difference was found between groups in quantitative parameters, including PI, TTP, and AUC. Conclusion: Contrast-enhanced ultrasound can provide valuable information of lymph node blood flow in the enhanced mode further, which can help to identify the tuberculous lymphadenitis and lymph nodes metastasis of PTC. The effectiveness needs further study and confirmation.